Implementasi Ilmu Kesejahteraan Sosial dalam Praktik Lapangan: Studi Pendampingan Emosional dan Sosial Anak Asuh di Panti Al Marhamah - Maharani, Nadya Puan; Triani, Emi; Ritonga, Fajar Utama (Yayasan Daarul Huda Kruengmane, 2025)
This community service activity aims to improve the quality of life of children at Al Marhamah Orphanage in Medan through social mentoring and capacity building in emotional and social development. The intervention employs a casework approach focused on addressing the emotional and social needs of the orphaned children, particularly a child with initials (A) who faces difficulties in social interaction. The process includes stages of engagement, assessment, intervention planning, implementation, evaluation, and termination. Through methods such as role-playing and motivational storytelling, (A) demonstrated increased confidence and improved communication skills over a three-week intervention period. Additionally, the activity strengthened communication and empathy between the mentor and the ward. It is hoped that this activity can serve as a model for human-centered and holistic social intervention efforts to empower orphaned children and contribute to social welfare development in Indonesia. This experience also enhanced the students' practical skills during fieldwork, fostering greater social awareness regarding the needs of underprivileged children.